Financial Solace: Malaysian Credit Counselling and Debt Management Agency Responses to COVID-19 Challenges - Ibtisam @ Ilyana Ilias; Nadzratun Naim Hammad Azizi; Noraiza Abdul Rahman; Mazlina Mahali (Emerging Science Journal, 2023)
This study evaluates the measures undertaken by the Credit Counselling and Debt Management Agency (AKPK) to assist those financially distressed due to their inability to meet their financial commitments amidst the COVID-19 pandemic. Adopting secondary analysis of qualitative data, relevant secondary data, including journal articles, annual reports, and newspaper articles, were analyzed. The study finds that measures adopted by AKPK in response to the COVID-19 pandemic include reinforcing the workforce, enhancing IT infrastructures, deploying digital platforms, using various media channels, introducing online apps, online portals, online webinars, online learning modules, and online payment facility for all debt management participants. AKPK is also entrusted with handling small and medium enterprises (SMEs) under the Small Debt Resolution Scheme. A dedicated SME Helpdesk is established to facilitate the process. AKPK’s continual support to provide financial aid is reflected in its collaborative effort with the banking industry under the Financial Management and Resilience Program and the Financial Resilience Support Program. However, the government should seriously consider strengthening personal data protection laws because of AKPK’s significant reliance on digital platforms. Similarly, appropriate government bodies must take quick action to address the digital divide issue and promote inclusion to reduce disparity in terms of access to online services offered by AKPK. Also, since certain individuals or SMEs with credit facilities with entities not regulated by Bank Negara Malaysia are deprived of this incentive, relevant regulators should undertake actions to provide a similar facility. This study is significant in that it provides lessons to be learned by other credit counseling and debt management agencies in adopting effective measures to enable them to adapt to the new normal. Doi: 10.28991/ESJ-2023-SPER-011 Full Text: PDF